When Marian sang : the true recital of Marian Anderson : the voice of a century - Ryan, Pam Munoz. (Scholastic Press, 2002)
An introduction to the life of Marian Anderson, extraordinary singer and civil rights activist, who was the first African American to perform at the Metropolitan Opera, whose life and career encouraged social change.